Taxonomic study of the genus Stilbops Förster from Japan (Hymenoptera: Ichneumonidae: Stilbopinae) - Watanabe, Kyohei; Maeto, Kaoru (Zootaxa, 2012)
The Japanese species of the genus Stilbops are taxonomically studied, with eleven species recognized. Three Russian Far East species, S. cavigena Kasparyan, S. mandibularis Kasparyan and S. orientalis Kasparyan are new to Japan. Six new species, S. auster sp. nov., S. coeloclypeus sp. nov., S. ezoensis sp. nov., S. japonicus sp. nov., S. michinokuensis sp. nov. and S. montanus sp. nov. are described. A key to Japanese species is provided. Their diversity and distribution patterns in the Eastern Palaearctic Region are also discussed.